God's rule : government and Islam - Crone, Patricia 1945- (Columbia University Press, 2004)
Patricia Crone's God's Rule is a fundamental reconstruction and analysis of Islamic political thought focusing on its intellectual development during the six centuries from the rise of Islam to the Mongol invasions. Based on a wide variety of primary sources?including some not previously considered from the point of view of political thought?this is the first book to examine the medieval Muslim answers to questions crucial to any Western understanding of Middle Eastern politics today, such as why states are necessary, what functions they are meant to fulfill, and whether or why they must be based on religious law.